Contemporary origami: a study of the art in fold and your practice mutability (Palíndromo, 2014)
This article aims to seek new forms of creative and artistic expression origa- mi nowadays. After crossing many gene- rations and countries, we noted that the functions of origami are much broader than simply making folding paper: the fol- ding has promoted a number of new buil- dings within the hybrid design and crea- tivity. Modularity, the collective, the build conscious, contemporary and innovation are intrinsic relations to artistic praxis that configure an adjacent scenario and subor- dinate to the main structure that govern this research project. We believe in the es- sence of origami as a tangible functionality for creative thinking.
Keywords: origami; comtemporary; art; crative; fold